2018
DOI: 10.1111/jvim.15228
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prespecified therapy escalation on plasma NT‐proBNP concentrations in dogs with stable congestive heart failure due to myxomatous mitral valve disease

Abstract: BackgroundTreatment targeted to achieve reduction in N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) improves outcomes in human congestive heart failure (CHF) patients.HypothesisA pre‐specified therapeutic algorithm that increased diuretic or pimobendan usage will reduce plasma NT‐proBNP concentrations in dogs with CHF secondary to myxomatous mitral valve disease (MMVD).AnimalsTwenty‐six dogs with clinically stable CHF secondary to MMVD.MethodsProspective, controlled before‐and‐after study. Dogs were exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Furthermore, a study on a myostatin antagonist used to counteract cardiac cachexia secondary to CHF has also been published [ 388 ]. In recent years, the evaluation of NT-pro BNP levels following the cardiological treatment has gained a lot of interest; in fact, low levels of this molecule indicate a better prognosis [ 389 , 390 ]. Cohort studies in veterinary medicine are rarely carried out because of high costs and long-time needing; in the period considered for this narrative review, only two have been found in the literature [ 391 , 392 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a study on a myostatin antagonist used to counteract cardiac cachexia secondary to CHF has also been published [ 388 ]. In recent years, the evaluation of NT-pro BNP levels following the cardiological treatment has gained a lot of interest; in fact, low levels of this molecule indicate a better prognosis [ 389 , 390 ]. Cohort studies in veterinary medicine are rarely carried out because of high costs and long-time needing; in the period considered for this narrative review, only two have been found in the literature [ 391 , 392 ].…”
Section: Resultsmentioning
confidence: 99%
“…An observational study of dogs with CHF showed that those with lower plasma NT‐proBNP measurements following initial treatment for CHF had longer survival times (Wolf and others 2012). A second study showed that the use of a prespecified treatment algorithm results in decreases in plasma NT‐proBNP (Hezzell and others 2018). However, whether the use of this algorithm to guide therapy results in improved outcomes in dogs remains unknown.…”
Section: Methods For Monitoring Chfmentioning
confidence: 99%
“…23 A pre-speciied treatment algorithm for CHF in dogs with MMVD, based on target reductions in circulating NT-proBNP measurements, has been demonstrated to be efective, although any inluence on prognosis remains untested. 24 However, an observational study suggested that the prognosis is better for dogs with CHF secondary to MMVD if circulating NT-proBNP measurements decrease in response to therapy. 25 In a study summarised on p 343 of this issue of Vet Record, Chan and colleagues measured short-term changes in cTnI following initiation of therapy for CHF secondary to MMVD.…”
Section: What You Need To Knowmentioning
confidence: 99%
“…Treatment with pimobendan has also been shown to result in decreases in heart size 23 . A pre‐specified treatment algorithm for CHF in dogs with MMVD, based on target reductions in circulating NT‐proBNP measurements, has been demonstrated to be effective, although any influence on prognosis remains untested 24 . However, an observational study suggested that the prognosis is better for dogs with CHF secondary to MMVD if circulating NT‐proBNP measurements decrease in response to therapy 25 …”
mentioning
confidence: 99%